HUBUNGAN PENGETAHUAN, PERSEPSI, DAN SIKAP MAHASISWA DENGAN PERILAKU PENCEGAHAN PENYEBARAN VIRUS CORONA - Johannes Bastira Ginting (Jurnal Keperawatan Priority, 2021)
Coronavirus disease (COVID-19) is an infectious disease caused by a coronavirus that can be transmitted from person to person, resulting in a worldwide pandemic. A person's knowledge, perceptions, and attitudes greatly affect the behavior of preventing Covid-19 by tightening the Covid-19 health protocol recommended by the Government. This study's aim was to determine the relationship between knowledge, perceptions, and attitudes of students with the behavioral of preventing the coronavirus. This type of research uses a cross-sectional design, research conducted at the University of Prima Indonesia, with consecutive sampling techniques. The analysis used univariate and bivariate with Chi-square test, the significance level was p<0.05. The knowledge variable of the majority of the population has a very good level of knowledge 72 people (72%) with a p-value of 0.002 < 0.05, the perception variable of the majority of the population has a very good perception 62 people (62%) with a p-value of 0.022 < 0.05, the variable the attitude of the majority of the population has a very good attitude 81 people (81%) with a p-value of 0.000 <0.05, the main behavioral variable who has very good behavior in preventing the spread of Covid-19 is 77 people (77%). From the results of the study, it was found that the variables of knowledge, perception, and student attitudes had a significant relationship with the behavior of preventing the spread of the coronavirus at Prima Indonesia University.